PENGARUH MORAL SENSITIVITY DAN MORAL COURAGE TERHADAP AUDIT JUDGMENT (Studi Empiris pada Auditor BPK RI - Perwakilan Provinsi Sumatera Utara) - Netanya Evelyn Berliana Damanik; Haryanto Haryanto (Diponegoro Journal of Accounting, 2026)
This study contributes to strengthening the internalization of the code of ethics and quality control to maintain the objectivity of the results of government financial audits. This study aims to identify empirical evidence and analyze the influence of moral sensitivity and moral courage on audit judgment among auditors at the North Sumatra Provincial Office of the Badan Pemeriksa Keuangan Republik Indonesia (BPK RI). Based on the Four-Component Model, this study focuses its testing on the initial and final stages, where the stages of moral judgment and moral motivation are assumed to have been institutionally standardized through BPK RI regulations. The research approach used is quantitative, utilizing primary data analyzed via multiple linear regression. The results indicate that, partially, moral sensitivity has a positive and significant effect on audit judgment, while moral courage was not found to have a significant effect on audit judgment. Theoretically, this study reinforces the relevance of the moral behavior model in the realm of public sector auditing. Practically, these results highlight the importance of developing ethics training based on real-world cases for BPK RI auditors.